Social networks and innovation: concepts, tools and recent empirical contributions - Cassi, Lorenzo (2007)
This paper reviews the most recent empirical literature dealing on social networks, knowledge diffusion and the innovative performance of firms. It aims to understand the extent to which the empirical literature on network and innovation addresses the key question of how social relations affect inter-firm knowledge flows. Reviewing the most recent and most significant empirical contributions in the field, we examine how social relations have been measured and defined and whether they affect inter-firm knowledge flows.